FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN INFORMED CONSENT DI RUANG RAWAT INAP RSUD DR M.YUNUS BENGKULU TAHUN 2011 - Septiyanti, Septiyanti (JURNAL MEDIA KESEHATAN, 2012)
Informed consent is an agreement by the patient to receive the treatment of or after the procedure provides more information, including the benefits and risks of treatment, alternative treatment, and prognosis. Based on the experiences during the service-man research at the Regional General Hospital (Hospital) Dr. M. Yunus Bengkulu nurse practitioner nursing action, just tell the nurse will be nursing actions and explain the aims of action, then ask for approval. So most patients and families do not know the side effects of actions, alternatives, risks and prognosis Tinda her. The study design was cross-sectional. Study sample were all nurses in the inpatient implementers: Jasmine, Chrysanthemum, and Lotus Hospital Flamboyan M Yunus Bengkulu in 2011, totaling 95 people. Univariate analysis was done with the frequency distribution, the bivariate chi-square test, and multivariate logistic regression models of multiple confounding. The results showed that almost all (76.8%) gave informed concent is not complete. Only leadership style variable-gammer mempu significant association with the implementation of informed consent (p = 0.02). Only the age variable to be confounding variables. Expected to carry out the briefing room head every morning with the nurse practitioner, the more stressed implementation of informed consent on each will implement nursing actions.